Radiographic assessment of age from epiphyseal fusion at knee joint of selected patients at a teaching hospital, Nepal - Raman Parajuli, Sudhir; KC, Subash; Maharjan, Sumi; Karki, Nabaraj (Journal of Chitwan Medical College, 2024)
Background: Determining age and sex in forensic science based on bone age estimation is becoming increasingly important because of the increase in unregistered documents and legal issues. For estimating the chronological age, radiographic analysis of knee is a reliable alternative with the assessment of three epiphyseal unions which includes distal femur, proximal tibia and proximal fibula at the same time. Method: An observational prospective study, including 80 patients, was conducted based on the sample of the anteroposterior radiographs of the knee of the patients visiting for X-ray knee through Emergency or Out Patient Departments within a period of one year (January 2021 to December 2021) at Manipal College of Medical Sciences, Pokhara, Nepal. In this study, anteroposterior radiographs of the knee were reviewed in subjects aged between 10 and 21 years old; 48 males and 32 females. Epiphyseal union was evaluated based on the ossification and epiphyseal scar. Result: The complete ossification of knee joint in males and females was first observed in all instances (100%) at the age groups of 18-19 and 17-19 years, respectively. Epiphyseal union in females occurred earlier than in males. Conclusion: The radiographic assessment of knee joint offers a valuable alternative as a non-invasive method for estimation of age.